Modeling and simulating a flow rack stock proposal to optimize the layout of the medicinal warehouse and reduce waste - Almeida, Matheus das Neves (2019)
This article has applied inventory management and warehouse layout techniques to reduce waste of defective products, unnecessary movement and processing in a warehouse of a distributor of drugs and related materials. For this purpose, the variables of the study were divided into two stages: the first concerns the layout dimensions of the warehouse, the provisions of current inventories and the dimensions of the packaging of products in stock; and the second refers to historical sales data such as the quantity sold and sales price of the products of the last 6 months. In addition, softwares was used, Allyphama to download data from sales history, Microsoft Excel to generate spreadsheets that aided in studies, AutoCad to generate the current and improved floor plans of the warehouse and SolidaWork to model and simulate the structure stock rack flow. As a result, this article investigated in situ the waste and found that the main ones were: waste of defective products (products due), unnecessary movement and processing. In view of this, we tried to improve the company's logistics system with the use of modeling and simulation of a proposed flow rack type structure, which obtained a significant reduction in the used area of approximately 35% and consequently reduce the aforementioned wastes. In this way, it is concluded that the application of inventory management techniques and change in layout for waste reduction is indeed beneficial for organizations and that this was proven in the case study using a drug distributor.